2022
DOI: 10.9778/cmajo.20210132
|View full text |Cite
|
Sign up to set email alerts
|

Subgroups of people who make frequent emergency department visits in Ontario and Alberta: a retrospective cohort study

Abstract: People who present frequently to emergency departments are a minority that account for disproportionate health care spending: 1 the highest 3% of this group comprise 30% of charges. 2,3 They are also high users of other health care [3][4][5][6] and are hospitalized and die more often than nonfrequent visitors to the emergency department, 7,8 suggesting a need for interventions that optimize patient outcomes and service allocation. 9 Effective interventions must recognize these patients' clinical and demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Our analysis corroborates previous work demonstrating that data-driven cluster analysis can discriminate subgroups of people who visit EDs frequently, which are comparable across Canadian provinces [ 14 , 46 ]. The 6.6% and 9.3% 365-day mortality we identified in “moderate” and “extreme” subgroups in B.C.were comparable to 4.7% to 8.8% mortality reported among people who made alcohol-related ED visits with increasing frequency in Ontario [ 13 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis corroborates previous work demonstrating that data-driven cluster analysis can discriminate subgroups of people who visit EDs frequently, which are comparable across Canadian provinces [ 14 , 46 ]. The 6.6% and 9.3% 365-day mortality we identified in “moderate” and “extreme” subgroups in B.C.were comparable to 4.7% to 8.8% mortality reported among people who made alcohol-related ED visits with increasing frequency in Ontario [ 13 ].…”
Section: Discussionsupporting
confidence: 90%
“…The increase in the number of hospital emergency department (ED) visits by older people is a worldwide phenomenon [ 13 , 14 , 15 ]. Furthermore, the figures will further grow over the coming years as the older population continues to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, seven studies found females were higher resource users than males and six found that sex-based differences were dependent upon other factors. Females were identified as higher resource users in multiple health care settings, including health services for all ages [16,17,21,22,28], health services for youth [29,30], primary care for all ages, and adult emergency department presentations [21,31].…”
Section: Sexmentioning
confidence: 99%
“…Three studies used comorbidity scores or indices -ie. the Charlson Comorbidity Index (CCI) -to determine the burden of comorbidities [16,17,21,22,28,32]. Patients with higher scores on the comorbidity indices were more likely to be hospitalized [28] and to see primary care and specialist visits [17].…”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation